Culturally Diverse Students’ Perspectives on Sexual Violence Policies: Recommendations for Culturally Sensitive Approaches to Prevention in Higher Education - Kennedy, Karen Dolores (Journal of interpersonal violence, 2024)
Culturally sensitive approaches in sexual violence prevention (SVP) refer to the proactive measures and strategies designed to address unique cultural circumstances impacting SVP. It focuses on fostering a culture of consent, respect, and equity and creating a safe and supportive environment for all individuals regardless of your identity. Increasing cultural diversity on university campuses poses unique challenges in preventing sexual violence (SV). Cultural diversity brings different perspectives, norms, and values regarding sex, sexuality, and gender roles. It can contribute to varying understandings of consent, differing attitudes toward SV, and diverse victimization experiences. These differences can create barriers to effectively addressing and preventing SV. The multiphase Culture and Perspectives on Sexual Assault Policy study, conducted at four universities in Eastern Canada, employed a qualitative research design involving focus groups with culturally diverse student participants. The findings revealed a strong desire for more education on sex, sexuality, SVP, and the intersections of culture. Additionally, the findings emphasize the importance of education and comprehensive prevention efforts that consider cultural differences, challenge gender normativity, debunk rape myths, and address the shame and secrecy associated with experiencing SV. These insights have significant implications for promoting a sense of community ownership, increasing the effectiveness and sustainability of prevention efforts, and helping to create a campus environment where all students feel safe, supported, and valued.